OC-034 The diagnosis of hepatic encephalopathy: test performance of novel paradigms. (23rd September 2015) - Hussein, M; Goh, Y; Youl, B; Jackson, C D; Morgan, M Y
Abstract : Introduction: The diagnosis of hepatic encephalopathy remains problematic, mainly because the current validated methods for assessing this syndrome, the PHES battery and spectral analysis of the EEG, are not universally available. Current interest has, therefore, focused on more novel computer-based systems, the most recent being the Inhibitory Control test (ICT), which, it is claimed, is able using a threshold of five incorrect lure responses, to diagnose hepatic encephalopathy with a sensitivity of 88% and a specificity of 77% (Bajaj et al, 2008). Experience with two other novel techniques viz: (i) the Sternberg paradigm (Sternberg, 1966), which is a computer-based, digit recognising task of memory scanning, and (ii) assessment of the ability to execute Smooth Pursuit Eye Movements (SPEM) (Montagnese et al, 2005) indicates that they have diagnostic potential. The aim of this study was to assess the performance of the ICT, Sternberg paradigm and SPEM for the diagnosis of hepatic encephalopathy, in patients with cirrhosis, both used singly and in combination. Methods: The patient population comprised 53 individuals (36 men, 17 women) of mean (range) age 57 (34–80) years, with biopsy-proven cirrhosis classified, using the West Haven criteria for mental state, the PHES test battery, and spectral analysis of the EEG, as either neuropsychiatrically unimpaired (n=34), or as having minimal (n=10) or overt (n=9) hepatic encephalopathy. The control population comprised 33 healthy volunteers (16 men, 17 women) of mean age 39 (21–70) years. The Sternberg and the ICT were performed using software programs supplied by the providers; SPEM assessments were performed using an infrared, video-based eye-tracking system. All the assessments were carried out under standard conditions, in a quiet, darkened room. Test thresholds, sensitivities and specificities were identified using ROC analysis. Binary logistic regression was used for a multivariate analysis of the test combinations. Results: Both healthy volunteers and patients found the ICT difficult to perform and its diagnostic performance was inferior to that of the other two techniques (Abstract 034 ). The best diagnostic performance was observed with the Sternberg/SPEM combination. Conclusion: The Sternberg test, used alone or in combination with SPEM, has excellent performance characteristics for the diagnosis of any degree of hepatic encephalopathy. The diagnostic performance of the ICT was disappointing.